Analisis Perupaan Situs Megalitik Gunung Padang di Cianjur, Jawa Barat - Savitri Putri Ramadina (Journal of Visual Art and Design, 2013)
Gunung Padang megalithic site at Desa Karyamukti, Cianjur, West Java is the biggest Megalithic site in Southeast Asia and situated in an area of 3132.15 m2. The site, which is located at 6°057'S 107°01'E about 50 kilometer southwest of Cianjur city in West Java, is shaped in punden berundak or terraced site which consisted of five terraces. This study is intended to be an endeavor to comprehend the architectural construction, visualization, and purpose of Gunung Padang site. The research was done by qualitative analysis and multidiscipline approaches, especially by using the theories of art history and art criticism. Based on the research, the whole site is an open megalithic structure which then divided into terraces bordered by big stone columns, and the area of the terraces is getting narrower toward the top of the site. Forerunner researches of Gunung Padang created assumptions that Gunung Padang site functioned as sacred place for animism ritual which was a common belief of Megalithic communities, and as a gathering place of chieftains for important discussions. The pattern of three and pattern of five, and symbols of Sunda Wiwitan applied in whole constructions and structures of Gunung Padang site. The abilities to build a majestic megalithic construction and the applications of aesthetic values and pattern of thoughts signifying that the people who built Gunung Padang site had advanced culture and civilization.